HOW CASE BASED LEARNING PROMOTES DEEP LEARNING IN PRE-CLINICAL YEARS OF MEDICAL STUDENTS? - Gul, Ambreen; Khan, Rehan Ahmed; Yasmeen, Rahila; Ahsan, Noorul Huda (Journal of Ayub Medical College Abbottabad, 2020)
Background: The study was conducted at Army Medical College, Rawalpindi to explore the factors in Case Based Learning (CBL) session responsible for promoting deep learning approach in medical students. Methods. A mix method research methodology with explanatory sequential design was adopted. In the quantitative part, the data was collected through a survey of second year medical students in which learning approaches were assessed using the Approaches and Study Skills Inventory for Students (ASSIST). Students were scored separately for the three approaches: surface, strategic and deep approach. In qualitative part; semi structured interviews were conducted with deep learners to explore the factors which help in promoting deep learning through Case-Based Leaning (CBL) guided inquiry approach. Interview data was transcribed, coded and thematic analysis was carried out. All quality assurance procedures of qualitative research such as credibility, trustworthiness, transferability, dependability and confirmability were ensured during the research. Results: Deep learners were identified by analyzing the ASSIST-inventory results. Qualitative analysis has revealed six main themes: active participation of the students in the CBL session, relevance of the case with their clinical practice, complexity of the case for future practice, intrinsic motivation, guided inquiry approach with tutor’s involvement, role playing and changes in learning approaches of the students were found responsible for inculcating deep learning approach in medical students in their pre-clinical years. Conclusion: The study concluded that by ensuring the factors that promote deep learning approach in medical students through Case Based Learning; it can be used as an effective strategy in teaching the content of basic science subjects during the pre-clinical years of medical students. Keywords: Deep learning; Case-Based Learning; Participation; Motivation